Geographical variation in the standard physiology of brushtail possums (Trichosurus): Implications for conservation translocations - Cooper, Christine; Withers, Philip; Munns, S.; Geiser, F.; Buttemer, W. (Oxford University Press, 2018)
Identifying spatial patterns in the variation of physiological traits that occur within and between species is a fundamental goal of comparative physiology. There has been a focus on identifying and explaining this variation at broad taxonomic scales, but more recently attention has shifted to examining patterns of intra-specific physiological variation. Here we examine geographic variation in the physiology of brushtail possums (Trichosurus), widely distributed Australian marsupials, and discuss how pertinent intra-specific variation may be to conservation physiology. We found significant geographical patterns in metabolism, body temperature, evaporative water loss and relative water economy. These patterns suggest that possums from warmer, drier habitats have more frugal energy and water use and increased capacity for heat loss at high ambient temperatures. Our results are consistent with environmental correlates for broad-scale macro-physiological studies, and most intra-generic and intra-specific studies of marsupials and other mammals. Most translocations of brushtail possums occur into Australia's arid zone, where the distribution and abundance of possums and other native mammals have declined since European settlement, leading to reintroduction programmes aiming to re-establish functional mammal communities. We suggest that the sub-species T. vulpecula hypoleucus from Western Australia would be the most physiologically appropriate for translocation to these arid habitats, having physiological traits most favourable for the extreme Ta, low and variable water availability and low productivity that characterize arid environments. Our findings demonstrate that geographically widespread populations can differ physiologically, and as a consequence some populations are more suitable for translocation to particular habitats than others. Consideration of these differences will likely improve the success and welfare outcomes of translocation, reintroduction and management programmes.